Teacher’s Roles in Teaching English to Students with Special Needs: Strategies, Challenges, and Impacts - Shofiyyah Nur Azka; Rafi Antar Saputra; Imas Wahyu Agustina; Dhini Aristy; Ajeng Amanatillah (STAIRS: English Language Education Journal, 2025)
Despite increasing global efforts to promote inclusive education, teaching English to students with special needs remains a significant challenge, including in the teacher’s role in shaping an inclusive learning environment. This study explores the critical role of teachers in special needs education by addressing three key issues: The teaching strategies employed, the challenges teachers encounter, and the impact on the learning process. Employing a qualitative and systematic approach, the study analyzed 30 peer-reviewed articles published within five years between 2020 and 2024. The analysis revealed that the most commonly applied strategies in teaching English to students with special needs were Individualized and Differentiated Instruction, Multisensory and Visual Learning, and Collaborative Teaching supported by professional development. Among the challenges identified, student-related factors emerged as the most prominent, followed by those related to teachers and systemic and policy issues. The learning impacts were classified into five thematic categories, each demonstrating positive, negative, and/or mixed implications. The review highlights the need for targeted teacher training, increased support structures, and stronger interprofessional collaboration.